ANALISIS EFISIENSI DINDING PENAHAN TANAH TYPE KANTILEVER DI KECAMATAN BABAHROT KABUPATEN ACEH BARAT DAYA - Bambang A. Sadat; Muhammad Isya; Hafnidar A. Rani (Prodi Magister Teknik Sipil Unsyiah, 2018)
The retaining wall is a retaining construction so that the soil does not slide. This construction is used for a cliff that is somewhat steep or erect, if without a retaining wall, the cliff will slide. Southwest Aceh Regency, especially in Babahrot-Blangkejeren road, Singgah Mata Mountains of Babahrot Subdistrict often experience landslide disaster. The cantilever type retaining wall is considered to be better against the structure and is suitable for use in mountain areas. However, a construction project generally requires substantial cost, therefore the selection of appropriate construction can provide efficiency to prevent loss and yields that are less than optimal. Based on that, it is necessary to analyze the cost estimation of retaining wall construction on mountain cliff, in this case using cantilever method. Functionally, the estimated cost is also intended for the calculation of the volume of work, the preparation of budget plans and scheduling in the implementation process of a construction project activity. This research was conducted to calculate dimension and cost estimation of cantilever type retaining wall construction with representation of segment that exist in surrounding mountain cliff of Babahrot-Blangkejeren road STA 13 + 850 - 13 + 895 Singgah Mata mountains at Babahrot Subdistrict, Southwest Aceh Regency. By obtaining wall dimension data from previous measurements and planning, this study analyzes and estimates the volume, cost, efficiency of the cantilever type retaining wall construction. From result of research indicate with planning, minimum safety factor required sf greater than 1,5, hence budget cost for cantilever type wall worth Rp. 1.109.438.000, -.